2020
DOI: 10.6061/clinics/2020/e2133
|View full text |Cite
|
Sign up to set email alerts
|

What You Gain and What You Lose in COVID-19: Perception of Medical Students on their Education

Abstract: The confirmation of a pandemic by the World Health Organization on March 11, 2020 proved that the SARS-CoV-2 virus would become a worldwide health issue (1). The Brazilian situation was no different from other countries: there was pressure on the health system and health workers. According to an article published by former Brazilian Health Ministry members, the country has been preparing itself for the COVID-19 disease since January 10, 2020 (2), and in many cities and states, isolation protocols have been set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 5 publications
7
53
0
10
Order By: Relevance
“…Three studies used more than one platform toll ( 7 , 8 , 9 ). One study did not show any information ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies used more than one platform toll ( 7 , 8 , 9 ). One study did not show any information ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chinelatto et al described the students’ perception of a medical program’s adaptation to remote learning ( 7 ). The graduation committee decided to interrupt educational activities for two weeks to give teachers time to reorganize their activities, outcomes, and educational strategies for the virtual environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift to distanced learning may serve as a footing for continued virtual teaching options even in the post-pandemic era. [11][12][13] Since completion of this study, the SPM has been incorporated into the clerkship curriculum and feedback has been positive. We have several strengths and limitations to our study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, amid the COVID-19 pandemic, there has also been a rapid shift to promote asynchronous learning through electronic platforms. [11][12][13] Electronic self-paced modules (SPM) may be a promising alternative given the flexibility it offers students and the appeal it has to the millennial generation. [14][15][16] Studies have compared TDS to SPM in teaching EBM to undergraduate MS, and have found SPM as effective as TDS in improving knowledge and attitudes.…”
Section: Introductionmentioning
confidence: 99%